Dent Disease 1 Presented Early with Bartter-Like Syndrome Features and Rickets: A Case Report - Cahyani Gita Ambarsari; Habibah Azzahra Putri Agianda; Meilania Saraswati; Jon Jin Kim (Case Reports in Nephrology and Dialysis)
Introduction: Dent disease (DD) is characterized by a triad of low-molecular-weight proteinuria, hypercalciuria, and nephrocalcinosis/nephrolithiasis. However, some cases were confounded by other clinical symptoms and signs, namely, hypokalemia and rickets, which resulted in misleading diagnoses. A diagnosis of DD could be delayed even in high-resource countries due to its variability of phenotypes and rarity, causing a lack of awareness in both medical practitioners and parents. Moreover, in low-resource countries, laboratory test limitations can hinder the diagnosis. Case Presentation: A thirteen-year-old boy presented with an acute episode of severe hypokalemia following vomiting due to COVID medication side effects. He had lower extremities weakness, salt craving, and polydipsia since childhood which were not thought to be unusual by the parents. He had a history of intrauterine polyhydramnios and maternal miscarriages. A physical examination showed hypotension, short stature, and genu valgum. His laboratory workup displayed hypokalemic metabolic alkalosis and increased urine potassium, chloride, transtubular potassium gradient, and calcium/creatinine ratio. He also had hypophosphatemia, hypomagnesemia, and decreased kidney function. Severe osteopenia was prominent on radiologic examination of all extremities. Subsequent laboratory samples sent overseas revealed low-molecular-weight proteinuria and a pathogenic variant in the CLCN5 gene confirming X-linked DD 1. Conclusion: This case report highlights the importance of considering DD in differential diagnoses of children with the pseudo-Bartter syndrome, that is, renal salt and potassium wasting, with or without hypercalciuria and nephrocalcinosis. Additionally, in children with rickets and proteinuria, urinary low-molecular-weight protein measurement could assist in screening for the possibility of DD, particularly in low-resource settings.